2019
DOI: 10.1177/0961203319878822
|View full text |Cite
|
Sign up to set email alerts
|

Association between CD40 polymorphisms and systemic lupus erythematosus and correlation between soluble CD40 and CD40 ligand levels in the disease: a meta-analysis

Abstract: Objective The aim of this study was to systematically review evidence regarding the association between CD40 polymorphisms and systemic lupus erythematosus and between soluble CD40 (sCD40) and CD40 ligand (sCD40L) levels and systemic lupus erythematosus. Methods We performed a meta-analysis on the association between CD40 rs4810495, rs1883832, and rs376545 polymorphisms and systemic lupus erythematosus risk and sCD40/sCD40L levels in patients with systemic lupus erythematosus and controls. Results Fourteen stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Much less is known about the possible role of sCD40 as a marker for CVD. Though sCD40 appears to be actively produced under physiological conditions (as suggested by comparatively large amounts of sCD40 found in urine of healthy individuals), 28 elevated plasma levels of sCD40 has nonetheless been described in pathologies such as systemic lupus erythematosus, 29 slow coronary flow phenomenon 30 and early Alzheimer's disease. 31 In the SUMMIT cohort, we found higher plasma sCD40 levels in individuals that had suffered a prior ischemic stroke or MI or were hypertensive.…”
Section: Discussionmentioning
confidence: 99%
“…Much less is known about the possible role of sCD40 as a marker for CVD. Though sCD40 appears to be actively produced under physiological conditions (as suggested by comparatively large amounts of sCD40 found in urine of healthy individuals), 28 elevated plasma levels of sCD40 has nonetheless been described in pathologies such as systemic lupus erythematosus, 29 slow coronary flow phenomenon 30 and early Alzheimer's disease. 31 In the SUMMIT cohort, we found higher plasma sCD40 levels in individuals that had suffered a prior ischemic stroke or MI or were hypertensive.…”
Section: Discussionmentioning
confidence: 99%
“…Soluble CD40 was found to be the strongest predictor of atherosclerotic plaque burden in the carotid artery bifurcation, among several other markers tested [30]. A role for sCD40 as a biomarker was also suggested in several other inflammatory diseases such as, e.g., ulcerative colitis [31], systemic sclerosis [32], and lupus erythematosus [33].…”
Section: Discussionmentioning
confidence: 88%
“…It is important to mention that the majority of the previously published studies concerning CD40 in SLE assessed its soluble form or encoding gene polymorphisms, and reported possible associations with SLE susceptibility without data about the role of peripheral CD40 + B cells. 9 However, Tokunaga et al. in his pilot study administrated rituximab in five patients with refractory SLE and reported a statistically significant decrease in peripheral CD40 + B cells from 94.6% to 55.5% after remission, with a dramatic improvement in SLEDAI.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 A recent meta-analysis proved the association between CD40 polymorphisms and SLE, and confirmed the important role of CD40 in SLE pathogenesis. 9 CD40 and CD40L interaction is essential to stimulate immunoglobulin class switching, as well as T cell–dependent B-cell response. 10 Following the interaction with CD40L, high expression of CD40 on antigen-presenting cells could enhance signalling in patients with autoimmune diseases such as SLE.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation